The Effect of Halal Awareness and Habit on Purchase Decisions with Religiosity as a Moderating Factor - Hasyim, Muhammad Hafidz; Vania, Amelindha (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study explores the influence of halal awareness and habit on halal product purchase decisions, with religiosity as a moderating variable. The research adopts a quantitative method with purposive sampling techniques. Data were collected through questionnaires distributed to Muslim consumers at Maliki Plaza, Malang. Using Structural Equation Modeling (SEM), the analysis revealed that halal awareness and habit significantly influence purchase decisions. Halal awareness enhances positive perceptions of halal products, while consumer habits create repetitive consumption patterns that strengthen loyalty. However, the results indicate that religiosity does not moderate the relationship between halal awareness, habit, and purchase decisions. These findings provide critical insights into relevant marketing strategies, particularly in enhancing halal education to promote awareness and consumer trust without relying on religiosity levels.